Determinants Of Contraceptive Use In The Mappurondo School Of Belief - Saleh, Sukardi; Nurhidaya, Nurhidaya; Akmal, Akmal; Muslimin, Irma; Mahardany, Beauty Octavia; Rahman, Kaprawi; Attalla, Sohayla (Jurnal Kesehatan Manarang, 2025)
The use of contraceptives among believers tends to be low. This can be attributed to traditional values that are still very strong in society, where the concept of extended family and the continuity of offspring are considered very important. Nevertheless, efforts have been made to provide understanding and education about the importance of family planning and reproductive health, so that people can choose wisely about the use of contraceptives according to their needs and values. This study aims to analyze the determinants of contraceptive use in adherents of the Mappurondo faith school in Mamasa Regency, West Sulawesi Province, using the 2022 National Population and Family Planning Agency's Family Data Collection Update data set. The population is all families adhering to the Mappurondo faith school in Mamasa district, a sample of 431 couples of childbearing age, with sample criteria that include married women between the ages of 15 and 49 years old, whether they use contraceptives or not. The analysis used is the chi-square test and the multivariate test. The results of the analysis showed that the variables of the age group of couples of childbearing age, Insurance Ownership, Welfare Level, Number of children born alive and got information about the family planning population program and family development from the officers statistically significantly related to the use of family planning in adherents of the Mappurondo faith school in Mamasa Regency, while the variables of Education Level and obtaining information about the population program program Family planning and family development from the media are not related to the use of family planning in the Mappurondo school of belief in Mamasa Regency (p>0.05). Variable Getting information about the KKBPK Program from officers is the most significant variable affecting contraceptive use, followed by the variable of Insurance Ownership. In conclusion, the variation of information about the KKBPK Program from officers did not provide a significant relationship with the use of contraceptives. Suggestions are hoped to improve the quantity and quality of communication, information, and education for family planning officers who provide counselling to the community of the Mappurondo faith.